2022
DOI: 10.1007/s10875-022-01264-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of SARS-CoV-2 Infection in Patients with Inborn Errors of Immunity: the Experience of the Italian Primary Immunodeficiencies Network (IPINet)

Abstract: COVID-19 manifestations range from asymptomatic to life-threatening infections. The outcome in different inborn errors of immunity (IEI) is still a matter of debate. In this retrospective study, we describe the experience of the of the Italian Primary Immunodeficiencies Network (IPINet). Sixteen reference centers for adult or pediatric IEI were involved. One hundred fourteen patients were enrolled including 35 pediatric and 79 adult patients. Median age was 32 years, and male-to-female ratio was 1.5:1. The mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(75 citation statements)
references
References 42 publications
5
70
0
Order By: Relevance
“…The majority of patients with IEI infected with SARS-CoV-2 reported in the literature were affected with primary antibody deficiency (PAD; n = 446) ( 3 9 , 26 , 28 , 30 , 32 , 33 , 35 , 37 , 38 , 43 68 ), including 290 with common variable immunodeficiency (CVID; 65% of all PAD), 71 with X-linked agammaglobulinemia (XLA; 16%), and 9 with autosomal recessive agammaglobulinemia (2%). The remaining 76 patients had other B-cell defects, including activated PI3Kdelta syndrome (APDS1: n = 6; APDS2: n = 1), nuclear factor-kappa B subunit 1 (NFKB1) deficiency ( n = 2), nuclear factor-kappa B subunit 2 (NFKB2) deficiency ( n = 4), TRNT1 (CCA-adding transfer RNA nucleotidyl transferase) enzyme deficiency ( n = 1), specific polysaccharide antibody deficiency (SPAD; n = 13), isolated IgA deficiency ( n = 17), IgG subclasses deficiency ( n = 3), or unspecified antibody deficiency ( n = 29).…”
Section: Primary Antibody Deficienciesmentioning
confidence: 99%
“…The majority of patients with IEI infected with SARS-CoV-2 reported in the literature were affected with primary antibody deficiency (PAD; n = 446) ( 3 9 , 26 , 28 , 30 , 32 , 33 , 35 , 37 , 38 , 43 68 ), including 290 with common variable immunodeficiency (CVID; 65% of all PAD), 71 with X-linked agammaglobulinemia (XLA; 16%), and 9 with autosomal recessive agammaglobulinemia (2%). The remaining 76 patients had other B-cell defects, including activated PI3Kdelta syndrome (APDS1: n = 6; APDS2: n = 1), nuclear factor-kappa B subunit 1 (NFKB1) deficiency ( n = 2), nuclear factor-kappa B subunit 2 (NFKB2) deficiency ( n = 4), TRNT1 (CCA-adding transfer RNA nucleotidyl transferase) enzyme deficiency ( n = 1), specific polysaccharide antibody deficiency (SPAD; n = 13), isolated IgA deficiency ( n = 17), IgG subclasses deficiency ( n = 3), or unspecified antibody deficiency ( n = 29).…”
Section: Primary Antibody Deficienciesmentioning
confidence: 99%
“…However, other studies have reported more severe courses of infection among CVID patients. An Italian study reported a 22% hospitalization rate among CVID patients (16). The study included individuals with various IEI and both children and adults, with patients with CVID being the largest patient group (16).…”
Section: Discussionmentioning
confidence: 99%
“…An Italian study reported a 22% hospitalization rate among CVID patients (16). The study included individuals with various IEI and both children and adults, with patients with CVID being the largest patient group (16). Though the overall mortality rate was similar to that of the background population, the age at death was significantly lower (all deaths were among adult patients) (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations